1992
DOI: 10.1177/106002809202600104
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Valproic Acid-Associated Hepatic Failure with Orthotopic Liver Transplantation

Abstract: Caution should be taken when initiating VPA therapy and clinicians should be familiar with the risk factors and clinical presentation of this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…However, prior studies have not been population‐based and did not capture a substantial number of patients undergoing liver transplantation. Studies that have included patients who underwent liver transplantation typically include few patients, such as case series 18, 19. In our analysis, post‐transplant survival was similar in the APAP and non‐APAP groups.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, prior studies have not been population‐based and did not capture a substantial number of patients undergoing liver transplantation. Studies that have included patients who underwent liver transplantation typically include few patients, such as case series 18, 19. In our analysis, post‐transplant survival was similar in the APAP and non‐APAP groups.…”
Section: Discussionmentioning
confidence: 78%
“…A novel finding in our study was that 42% of liver transplants for non‐APAP liver injury was attributed to just 4 drugs: isoniazid, propylthiouracil, phenytoin, and valproate. Severe liver injury due to these drugs has been well described 10–19. However, prior studies have not been population‐based and did not capture a substantial number of patients undergoing liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The cases reported here were 14, 20, and 21 years old when VPA was introduced. Three other cases of survival after LT for VPA‐ALF also have been reported; these patients were 19, 20, and 23 years old at the time of transplantation . In contrast, in Mindikoglu et al's series, 15 of 17 patients were less than 8 years old, with the oldest being 16 years old.…”
mentioning
confidence: 94%
“…Serum amylase, lipase, liver function profile, electrolytes, glucose, and coagulation parameters should be quantified. Signs and symptoms associated with fulminant hepatic failure should be closely monitored because of numerous reports of fatalities from VPA-associated hepatic failure [43,80,85]. Bell et al reported a case of a 23-year-old woman who developed fulminant hepatic failure secondary to VPA toxicity that required orthotopic liver transplantation [85].…”
Section: How Do You Manage Patients With Valproic Acid Toxicity?mentioning
confidence: 99%